2015
DOI: 10.1007/s00345-015-1753-7
|View full text |Cite
|
Sign up to set email alerts
|

Early repeated ureteroscopy within 6–8 weeks after a primary endoscopic treatment in patients with upper tract urothelial cell carcinoma: preliminary findings

Abstract: 2nd-look-URS-related CDR in conservatively treated UTUC patients was 51.2 %. 2nd-look-URS outcomes affected the findings of both subsequent endoscopic evaluation and mRFS. Further studies are needed to confirm the benefits of this approach in terms of patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…15 Addressing this issue, Villa and colleagues, in a novel study, examined the role of early repeat URS at 6 weeks and the association of tumor present at second look with outcomes. 16 They found that the presence of tumor 6 weeks later predicted poor subsequent recurrence-free rates. One wonders if this truly represents early recurrence, or instead an incomplete identification and resection of tumor at the initial endoscopy, and therefore incomplete treatment.…”
Section: Indications and Outcomes Endoscopic Managementmentioning
confidence: 99%
“…15 Addressing this issue, Villa and colleagues, in a novel study, examined the role of early repeat URS at 6 weeks and the association of tumor present at second look with outcomes. 16 They found that the presence of tumor 6 weeks later predicted poor subsequent recurrence-free rates. One wonders if this truly represents early recurrence, or instead an incomplete identification and resection of tumor at the initial endoscopy, and therefore incomplete treatment.…”
Section: Indications and Outcomes Endoscopic Managementmentioning
confidence: 99%
“…In a retrospective study of 41 UTUC patients, Villa et al [14] evaluated the cancer detection rate of a second-look URS performed within 60 days of the first URS with laser ablation. The cancer detection rate at second-look URS was 51.2%, which emphasizes the necessity of a second look at 6–8 weeks and a stringent follow-up.…”
Section: Treatment Selectionmentioning
confidence: 99%
“…Nevertheless, biopsy grading may be used to improve tumor staging: 68–100% of grade 1 tumors on biopsies are non-muscle invasive tumors while 62–100% of grade 3 are ≥ pT2 tumors ( 20 ). Recently, the impact of cancer detection rate during early repeated flexible ureteroscopy (2nd-look-ureteroscopy within 60 days of the first ureteroscopy) has been recently reported in patients initially treated with endoscopic laser ablation ( 22 ). At a median follow-up of 27.6 months, massive tumour (defined as a tumour not completely removable with a kidney sparing approach) RFS rates were 88% and 48% in patients with negative and positive 2nd-look-ureteroscopy, respectively.…”
Section: Preoperative Predictive/prognostic Factors For Utucmentioning
confidence: 99%